4x-3(-x+4)=23

Simple and best practice solution for 4x-3(-x+4)=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3(-x+4)=23 equation:



4x-3(-x+4)=23
We move all terms to the left:
4x-3(-x+4)-(23)=0
We add all the numbers together, and all the variables
4x-3(-1x+4)-23=0
We multiply parentheses
4x+3x-12-23=0
We add all the numbers together, and all the variables
7x-35=0
We move all terms containing x to the left, all other terms to the right
7x=35
x=35/7
x=5

See similar equations:

| ||x=1 | | 5x-2x-2=6x+10 | | 7/2x=x+5 | | 4p-5=28 | | 8-5w=-39 | | 100+4p=7p | | -3(4-3x)=7x+9 | | 2x=-12=-10 | | 6(3n+5)=9(7n+4+8= | | 3+5(2x-4)=5x+3 | | 3x+28=25 | | 71x-2=(51x+4)+17x | | 4x-5(-2x+3)=-169 | | 7x/2+8=96 | | 110a=150+85a | | -4x+6=70 | | 17v-8v=27 | | 4x2+10x+6= | | 25y+15-16y=7y+11,5y-9 | | (x+5)°=(x-13)° | | (-x)+7=-2x+1 | | 12x+-6=15+5x | | 8-7x-7x=-90 | | x-30+.5x+15+2X-22=180 | | -4x+6x-6=2(x-4)-2 | | 87=5x+3(5x+9) | | 4y+9=3y+5 | | (7x-9)=(5x+9) | | 1/15p-1/2=1/5p-3/10 | | 3b-9=4b+28 | | 2(x+5)=6x-4-2x+2 | | 3x=4=4x=-38 |

Equations solver categories